Energy Dreams : Of Actuality - Marder, Michael (Columbia University Press, 2017)
The question of energy is among the most vital for the future of humanity and the flourishing of life on this planet. Yet, only very rarely (if at all) do we ask what energy is, what it means, what ends it serves, and how it is related to actuality, meaning-making, and instrumentality. Energy Dreams interrogates the ontology of energy from the first coinage of the word energeia by Aristotle to the current practice of fracking and the popularity of "energy drinks." Its sustained, multi-disciplinary investigation builds a theoretical infrastructure for an alternative energy paradigm.This study unhinges stubbornly held assumptions about energy, conceived in terms of a resource to be violently extracted from the depths of the earth and from certain living beings (such as plants, converted into biofuels), a thing that, teetering on the verge of depletion, sparks off movement and is incompatible with the inertia of rest. Consulting the insights of philosophers, theologians, psychologists and psychoanalysts, economic and political theorists, and physicists, Michael Marder argues that energy is not only a coveted object of appropriation but also the subject who dreams of amassing it; that it not only resides in the dimension of depth but also circulates on the surface; that it activates rest as much as movement, potentiality as much as actuality; and that it is both the means and the end of our pursuits. Ultimately, Marder shows that, instead of being grounded in utopian naïveté, the dreams of another energy-to be procured without devastating everything in existence-derive from the suppressed concept of energy itself.